Use of an absorbable embolization material for reversible portal vein embolization in an experimental model. Issue 10 (1st August 2016) - Olthof, P B; Huisman, F; van Golen, R F; Cieslak, K P; van Lienden, K P; Plug, T; Meijers, J C M; Heger, M; Verheij, J; van Gulik, T M
Abstract: Background: Portal vein embolization (PVE) is used to increase future remnant liver size in patients requiring major hepatic resection. PVE using permanent embolization, however, predisposes to complications and excludes the use of PVE in living donor liver transplantation. In the present study, an absorbable embolization material containing fibrin glue and different concentrations of the fibrinolysis inhibitor aprotinin was used in an experimental animal model. Methods: PVE of the cranial liver lobes was performed in 30 New Zealand White rabbits, which were divided into five groups, fibrin glue + 1000, 700, 500, 300 or 150 kunits/ml aprotinin, and were compared with a previous series of permanent embolization using the same experimental set-up. Caudal liver lobe hypertrophy was determined by CT volumetry, and portal recanalization was identified on contrast-enhanced CT images. Animals were killed after 7 or 42 days, and the results were compared with those of permanent embolization. Results: PVE using fibrin glue with aprotinin as embolic material was effective, with 500 kunits/ml providing the optimal hypertrophic response. Lower concentrations of aprotinin (150 and 300 kunits/ml) led to reduced hypertrophy owing to early recanalization of the embolized segments. The regeneration rate over the first 3 days was higher in the group with 500 kunits/ml aprotinin than in the groups with 300 or 150 kunits/ml or permanent embolization. In the 500-kunits/ml group, four of five animals showed recanalization 42 days after embolization, with minimal histological changes in the cranial lobes following recanalization. Conclusion: Fibrin glue combined with 500 kunits/ml aprotinin resulted in reversible PVE in 80 per cent of animals, with a hypertrophy response comparable to that achieved with permanent embolization material. Surgical relevance Portal vein embolization (PVE) is used to increase future remnant liver volume in patients scheduled for major liver resection who have insufficient future remnant liver size to perform a safe resection. The current standard is PVE with permanent embolization materials, which renders patients found to have unresectable disease prone to complications owing to the permanently deportalized liver segments. Absorbable embolization might prevent the PVE-associated morbidity and lower the threshold for its application. In this study, PVE using fibrin glue and aprotinin resulted in an adequate hypertrophy response with 80 per cent recanalization after 42 days. Considering the minor histological changes following recanalization of embolized segments and potentially preserved function, reversible PVE might also be applied in living donor liver transplantation. Abstract : A temporary plug